A Study of Fungal Diseases Occurring on Stored Tomatoes of Balkhu Agriculture and Vegetable Market, Nepal - Shakya, Bimala; Aryal, Hari Prasad (Journal of Natural History Museum, 2020)
Tomatoes are one of the most widely produced and consumed vegetable in Nepal. Fungal pathogens deteriorate the quality and quantity of tomato and cause health hazards to the consumers as well as economic loss to the traders. This study was carried out to identify some fungal diseases associated with post-harvest deterioration of stored tomato fruits in Balkhu Agriculture and vegetable Market of Kathmandu, Nepal. Collected samples were cultured in Potato Dextrose Agar (PDA) media in complete randomized design. Fifteen species of fungi namely Alternaria alternata, A. solani, Aspergillus niger, Botrytis cinerea, Fulvum fulva, Colletotrichum truncatum, Curvularia spicifera, Fusarium oxysporum, Dipodascus geotrichum, Mucor mucedo, Penicillium chrysogenum, Phytophthora infestans, Boeremia exigua, Pythium aphanidermatum and Rhizopus stolonifer were identified. These were responsible for 14 different diseases of Alternaria fruit rot, Anthracnose, Black mold rot, Botrytis Bunch Rot, Damping off/ fruit rot, Drechslera mold, Fusarium rot, Mucor rot, Penicillum rot, Boeremia blight, Phytophthora rot, Rhizopus rot, Russet, and, Sour rot. The presence of these fungi and corresponding rot diseases on stored tomato indicates the need for management of fungi, farm sanitation and improved market in order to prevent field-to-storage transmission of pathogen.